2022
DOI: 10.1117/1.jmi.9.4.047501
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study to evaluate tools to collect pathologist annotations for validating machine learning algorithms

Abstract: Purpose: Validation of artificial intelligence (AI) algorithms in digital pathology with a reference standard is necessary before widespread clinical use, but few examples focus on creating a reference standard based on pathologist annotations. This work assesses the results of a pilot study that collects density estimates of stromal tumor-infiltrating lymphocytes (sTILs) in breast cancer biopsy specimens. This work will inform the creation of a validation dataset for the evaluation of AI algorithms fit for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…eeDAP is a software-hardware interface to register microscope slides to WSI images, collect pathologist annotations, and evaluate WSI technology. Prior registration accuracy studies 14 and pathologist annotation studies 17 have demonstrated the accuracy, stability, and utility of eeDAP as a data-collection tool. This work shows that with new hardware eeDAP is still capable of registration accuracy within 5 µm on a glass slide 97% of the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eeDAP is a software-hardware interface to register microscope slides to WSI images, collect pathologist annotations, and evaluate WSI technology. Prior registration accuracy studies 14 and pathologist annotation studies 17 have demonstrated the accuracy, stability, and utility of eeDAP as a data-collection tool. This work shows that with new hardware eeDAP is still capable of registration accuracy within 5 µm on a glass slide 97% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…The new hardware was motivated by a pilot study of the High Throughput Truthing (HTT) project [15][16] . Results from the pilot study demonstrated the need to improve overall speed of eeDAP to make its use comparable to that of our web application data collection platforms 17 . We combine the data collected on the new hardware with the 2018 data and perform a multi-reader multi-case (MRMC) analysis to obtain estimates of reader and case variance components for sizing future studies.…”
Section: Introductionmentioning
confidence: 99%
“…New tools are emerging for estimating truth from panels of expert readers, including improved approaches to reader training to reduce reader variability, improved collection interfaces, and statistical analysis tools. 36,37 Similarly, better approaches are emerging for collecting data from humans who are serving as "study" readers in a task-based assessment. These also include improved training methods and data collection interfaces that facilitate the collection of more precise reader data on a finer measurement scale.…”
Section: Methodsmentioning
confidence: 99%
“…Pathologists' visual assessment of TILs in biopsies and surgical resections of human epidermal growth factor receptor-2 positive (HER2+) and triple-negative breast cancer (TNBC) patients results in a (TILs) score ranging from 0 to 100 [2]. However, there is a great deal of variability among pathologists in estimating the TILs score due to the visualdependent nature of the estimation task [3][4][5]. Advances in ML algorithms in digital pathology [6] pave the way for designing algorithms to automatically generate TILs scores from whole slide images (WSIs) of breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%